2002
DOI: 10.1159/000057693
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Potential of Hematopoietic and Neural Stem Cells: Unique or All the Same?

Abstract: Like many other animals, mammals develop from fertilized oocytes – the ultimate stem cells. As embryogenesis proceeds, most cells lose developmental potential and eventually become restricted to a specific cell lineage. The result is the formation of a complete and structured mature organism with complex organs composed of a great variety of mature, mostly mitotically quiescent effector cells. However, along the way, some exceptional cells, known as somatic stem cells (SSCs) are set aside and maintain a high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
1
8
1
1
Order By: Relevance
“…Limiting dilution analysis of Lin – , Sca‐1 + , c‐kit + cells has shown that this cell population is capable of long‐term and multilineage hematopoietic reconstitution of lethally irradiated mice (25). Our own experiments revealed that 20 cells with the lin – , c‐kit + Sca‐1 + phenotype are sufficient to repopulate the hematopoietic system of lethally irradiated mice recipients (32).…”
Section: Isolation Of Hematopoietic Stem Cellsmentioning
confidence: 99%
“…Limiting dilution analysis of Lin – , Sca‐1 + , c‐kit + cells has shown that this cell population is capable of long‐term and multilineage hematopoietic reconstitution of lethally irradiated mice (25). Our own experiments revealed that 20 cells with the lin – , c‐kit + Sca‐1 + phenotype are sufficient to repopulate the hematopoietic system of lethally irradiated mice recipients (32).…”
Section: Isolation Of Hematopoietic Stem Cellsmentioning
confidence: 99%
“…HSCs into 3.5-day-old murine blastocysts, chimaeric foetal and adult mice are generated (Geiger et al, 1998;Harder et al, 2002;Kirchhof et al, 2002 …”
mentioning
confidence: 99%
“…Es sind seltene Zellen mit einem hohen regenerativen Potenzial, die in vitro angereichert werden können [3]. Weniger als 20 isolierte hämatopoeti-sche Stammzellen können das komplette Blutsystem letal bestrahlter Tiere lebenslang repopulieren [4].…”
Section: Somatische Stammzellenunclassified